Analysis of the swing motion on knuckling shot in soccer - Hong, S.; Chung, C.; Sakamoto, K.; Asai, T. (Procedia Engineering, 2011)
The purpose of this study is to analyze the swing characteristics of the kicking leg in order to elucidate the technical mechanisms of the knuckling shot. The tendency to impact with the heel pushed out towards the inside of the foot was considered. Hip external rotations in the knuckling shot exerted greater external rotation torque of the hip joint than the other shots. In this manner, it can be considered that compared to the other shots, the knuckling shot exerts a greater external rotation torque on the hip and has a tendency to impact with the heel pushed towards the inside of the foot.